Retina Görüntülerinde Yaşa Bağlı Makula Dejenerasyonu'nun Bilgisayar Destekli Tespiti - Çalık, Esra; Doğan, Buket; Uçan, Osman Nuri (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Bu çalışmada, Fundus Floresein Anjiografi (FFA) yöntemi ile elde edilen retina gorüntüleri üzerinde Yaşa Bağlı Makula Dejenerasyonu (YBMD) hastalığının Bilgisayar Destekli Tespit (BDT) işleminin gerçekleştirilmesi amaçlanmıştır. Toplam 87 gorüntü kullanılarak oluşturulan veri seti üzerinde BDT ile hastalık tespit işlemleri gerçekleştirilmiştir. Yapılan çalışmanın amacı, geliştirilen BDT sistemi ile YBMD hastalığından etkilenen ilgili bölgelerin (İB) işaretlenerek, bu bölgelerin tespit edilmesini sağlamaktır. Böylelikle, işaretlenen bölgelerin göz hekimleri tarafından daha kısa sürede değerlendirilmesi ve hasta takibini kolaylaştırması mümkün olacaktır. BDT sisteminin ön işleme aşamasında morfoloik görüntü işleme, bölütleme aşamasında sobel kenar algılama filtresi, İB'lerin belirlenmesi aşamasında çıkarılan özelliklere göre İB olabilecek bölgelerin tespiti ve karar verme aşamasında optik diskin eliminasyonu yapılarak, ilgili bölge olarak etiketlenmiş yapının belirlenmesi işlemleri gerçekleştirilmiştir. Geliştirilen BDT sistemi ile elde edilen sonuçlar uzman bir göz hekimi tarafından kontrol edilerek, BDT sisteminin elde ettiği performans kriterleri sonuç olarak belirtilmiştir. Sonuç olarak, 74 (DP ve DN) doğru tespit, 13 (YP ve YN) yanlış tespit sonucu, geliştirilen BDT sistemi ile %85,05 doğruluk yüzdesine ulaşılmıştır.

This work aims to realize Age related macular degeration (ARMD) detection process on the retinal images obtained by the Fundus Floresein Angiography (FFA). Critic area process has been performed by Computer Aided Detection (CAD) system which was detected on data sets generated with the use of 87 images of total. The purpose of this work, regions of interest affected by ARMD disease is to provide detection with CAD system. Thus, monitoring of the treatment of the patient can be made by doctors labeled on retinal images. This study intends to provide the detection of ARMD by separating structure like blood vessels, optic disc from retinal images using pre- processing techniques as bands of color separation, histogram processes of images. In CAD pre- processing stage the areas that can be ARMD are made to be more clearer and sharpener and edge filters and dilation algorithms are used to perform successful segmentation process. At the end of the pre- processing and segmentation stages, regions of interest are labeled based on feature extracted. Regions of interest are issued to characteristics, optic disc has been eliminated by the algorithm developed. In the final stage the regions of interest are labeled according to these features. Accuracy of system is tested by ophthalmologist as controlling the ARMD and healthy retinal images labeled by CAD process. Finally, 74 (TP and TN) positive, 13 (FP and FN) negative results in detection were reached with the developed CAD system. In detection of ARMD study, using performance evaluation criteria, the accuracy of the algorithm is obtained as 85,05%.
Computer Aided Detection of Age Related Macular Degeneration in Retinal Images
Keywords: YBMD; BDT Sistemi; Medikal Görüntü İşleme; Morfolojik Yapılandırma; ARMD; CAD System; Medical Image Processing; Morphological Reconstruction